Transapical TAVR and Off-pump Coronary Artery Bypass: How to Tackle a Porcelain Aorta from Two Sides - Scarpanti, Matteo; Gallingani, Alan; Agostinelli, Andrea; Formica, Francesco; Nicolini, Francesco (Archives of Clinical and Medical Case Reports, 2022)
Here we report the case of a 77-year-old man who presented to our department with a history of aortic stenosis and newly discovered left main disease. He had a past medical history relevant for peripheral artery disease and the latest CT scan highlighted a severely calcified aorta circumferentially throughout its whole course (so called “porcelain aorta”). To find a definitive solution for the patient’s presenting problem, he underwent Off-Pump Coronary Artery Bypass (OPCAB) and, subsequently, Transapical Transcatheter Aortic Valve Replacement (TATAVR). We believe that, in selected patients presenting with aortic stenosis and coronary artery disease, for whom the risk for either percutaneous intervention or surgical aortic valve replacement are deemed too high, a hybrid approach with OPCAB and TA-TAVR is a very effective solution in tackling such a critical clinical scenario.